1997
DOI: 10.1073/pnas.94.22.11869
|View full text |Cite
|
Sign up to set email alerts
|

Extensive purification of a putative RNA polymerase I holoenzyme from plants that accurately initiates rRNA gene transcription in vitro

Abstract: RNA polymerase I (pol I) is a nuclear enzyme whose function is to transcribe the duplicated genes encoding the precursor of the three largest ribosomal RNAs. We report a cell-free system from broccoli (Brassica oleracea) inf lorescence that supports promoter-dependent RNA pol I transcription in vitro. The transcription system was purified extensively by DEAE-Sepharose, Biorex 70, Sephacryl S300, and Mono Q chromatography. Activities required for pre-rRNA transcription copurified with the polymerase on all four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 48 publications
7
54
0
Order By: Relevance
“…TIF-IA has been shown to be part of the Pol I 'holoenzyme', the enzyme moiety that is associated with most, if not all, factors required for transcription initiation (Saez-Vasquez and Pikaard, 1997;Seither et al, 1998;Albert et al, 1999). Moreover, TIF-IA has been shown to interact with TIF-IB/SL1 (Miller et al, 2001), which suggests that TIF-IA bridges both protein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…TIF-IA has been shown to be part of the Pol I 'holoenzyme', the enzyme moiety that is associated with most, if not all, factors required for transcription initiation (Saez-Vasquez and Pikaard, 1997;Seither et al, 1998;Albert et al, 1999). Moreover, TIF-IA has been shown to interact with TIF-IB/SL1 (Miller et al, 2001), which suggests that TIF-IA bridges both protein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…(78,79) Transient and in vitro transcription assays have shown that Arabidopsis and Brassica rRNA promoters can function with the RNA Polymerase I transcription machinery of the other species. (78,80) Silenced rRNA genes in Arabidopsis and Brassica allotetraploids were reactivated by chemical inhibitors for DNA methylation and/or histone deacetylation, suggesting that rRNA genes are silenced by DNA and histone modifications presumably associated with inactive chromatin structure. (81) Collectively, the data suggest that rRNA gene silencing acts on chromosomal loci that result in cooperative silencing of rRNA genes.…”
Section: Activation Of Transposons and Changes In Dna Methylation In mentioning
confidence: 99%
“…Consistent with this notion, the enhancer imbalance model (76) suggests that, in Xenopus interspecific hybrids, dominant rDNA clusters have stronger enhancers that titrate the available transcription factors so that the rDNA clusters with weaker enhancers are inaccessible to the transcription activators and are not transcribed. Although this model is not supported by transient and in vitro and in vivo transcription assays in plants, (78,80) the involvement of species-specific factors should not be ignored. These factors may represent upstream regulators in a regulatory pathway.…”
Section: Transcriptional Regulation In Allopolyploidsmentioning
confidence: 99%
“…Primer tis maps the transcription initiation site accurately, TIS (Figure 9C, lanes 5-7;Saez-Vasquez and Pikaard, 1997) and allows quantification of pre-rRNA precursors, whereas primer p accurately maps the primary cleavage site, P (Figure 9C, lanes 11-13;Saez-Vasquez et al, 2004) and allows quantification of processed pre-rRNA precursors. To compare the ratio between primary pre-rRNA and cleaved prerRNA (TIS/P) in WT and Atnuc-L1 plants, tis and p primers were added simultaneously to the same primer extension reactions ( Figure 9C, lanes 8 -10).…”
Section: Atnuc-l1 Gene Disruption Affects Rrna Synthesismentioning
confidence: 99%